JQuery Hotshot - Wellman, Dan (Packt Publishing, Limited, 2013)
This book takes a hands-on, tutorial-style approach that walks you step -by -step through 10 individual projects that each focus on producing a specific, real-world product or application.This book is aimed primarily at front-end developers, preferably already with a little jQuery experience, or those people that simply want to build on their existing skills with jQuery.